Logic, rationality, and interaction : 7th International Workshop, LORI 2019, Chongqing, China, October 18-21, 2019, Proceedings /: 7th International Workshop, LORI 2019, Chongqing, China, October 18-21, 2019, Proceedings. (2019) - Unknown
No abstract available